Social stress in young people with specific language impairment - Wadman, Ruth; Durkin, Kevin; Conti-Ramsden, Gina (Elsevier, 2010)
Social interactions can be a source of social stress for adolescents. Little is known about how adolescents with developmental difficulties, such as specific language impairment (SLI), feel when interacting socially. Participants included 28 adolescents with SLI and 28 adolescents with typical language abilities (TL). Self-report measures of social stress, social skills and social acceptance were obtained. Participants with SLI reported experiencing significantly more social stress than did participants with TL. Both groups judged themselves as having adequate social skills and positive social acceptance. Expressive language ability was negatively associated with social stress, but did not predict social stress when social factors were included in the regression model. Perceived social skills and social acceptance scores predicted social stress, in that poorer scores predicted more social stress. Despite perceiving themselves as having adequate social skills and as being socially accepted, social interactions are nonetheless a source of stress for adolescents with SLI.